Economic Effects Of The Philosophical Concept Of Community - Vera, Alfonso (REVISTA PROCESOS DE MERCADO, 2020)
Introductory textbooks in the History of Economic Thought in use at colleges and universities devote little space to Scholasticism and its influence. Even those that do not start straight with the Physiocrats, Thomas Aquinas appears stuck between Ancient Greek Philosophers and Thomas Mun. Scholasticism with “medieval” economic thought characterized as primitive and focused on “obsolete” issues like usury and just price. Sometimes it is even categorized among the schools that promote State intervention1. This was not the opinion of F.A. Hayek, who appreciated some Scholastic authors as part of the individualistic tradition of Western civilization rooted on the legacy of Ancient Greeks and Romans like Pericles, Thucydides, Cicero and Tacitus2. In his famous Road to Serfdom (1944) F.A. Hayek assumed that Western Civilization had abandoned the right road and the individualistic tradition by the last quarter of the XIX Century. The abandoned road that Hayek refers to is that grounded on Greek, Roman and Medieval tradition and later paved by the ideas of authors like Cobden, Bright, De Tocqueville, Lord Acton, Adam Smith, Hume, Locke or Milton3. Hilaire Belloc4 located the abandonment of the liberal tradition around the same historical time. He would have agreed with most of the names in Hayek´s list, especially Cobden and Bright, but would have added those of radicals like Fox and Cobbett. Regarding more far away sources of Western thought, he would have included Aristotle, Aquinas and the Spanish Jesuit Francisco Suárez.Some of the authors mentioned above represent different traditions in the political philosophy. These traditions could be referred as the “old” and the “new”, following Leo Strauss in the idea of Machiavelli as the turning point. This essay approaches the influence of the political philosophy in the changes referred by Hayek and Belloc by examining the differences between the old and the new concept of community.